Remembering the dead: enhancing the commemoration qualities of ecological cemeteries - Corrie, Brian (Kansas State University, 2018)
Cemeteries are often perceived as static landscapes containing markers of our collective past. Although this characterization encapsulates the function of a funerary landscape, it does not account for the experiential and restorative qualities these spaces can provide. Memorials can act as a bridge, connecting us to the departed by allowing for the projection of remembrance onto a tangible medium. At the turn of the 20th Century, the funerary industry in the United States began to define itself as a profession with the introduction of preservation technologies. Although these methods were not initially accepted, they are now considered to be the modern societal norm. Recently, there has been a revival in natural burial practices as an alternative to the traditional casket-embalming method. Ecological cemeteries incorporate natural burial practices as a way to provide their clientele with a sustainable, natural way of interment. This burial process includes a basic grave, shroud or biodegradable enclosure for the body and no toxic embalming fluids as a way of ensuring the body returns to the earth while enhancing the natural ecological cycle. These natural burial sites do not display rows of gravestones but are rather evocative landscapes meant to provide consolation without the environmental drawbacks that modern burial practices pose. This more sustainable, but often invisible, practice uses little physical denotation for mourners to identify their loved ones. Cemetery design needs to retain the emotive and restorative qualities of funerary landscapes while accommodating the growing trend of natural burials. This project aims to create a design framework that can inform existing and future cemeteries by investigating burial norms, how people commemorate, the experiential design of funerary landscapes, and the evolution of natural burials. These findings were combined with precedent studies, surveys, interviews, and design guidelines. The resultant design guidelines were then applied to an existing cemetery, Sunrise Cemetery located in Manhattan, Kansas. The proposed funerary landscape will provide mourners with a meaningful place for commemoration while maintaining healthy ecologies and could lead to a considerable shift in burial norms in the United States by demonstrating how a variety of remembrance practices can be accommodated in an ecological cemetery.
Keywords: Landscape architecture; Burial; Commemoration; Design; Natural